2017
DOI: 10.1097/rli.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Volumetry at Contrast-Enhanced Magnetic Resonance Angiography

Abstract: 1.1. Objectives Bicuspid aortic valve (BAV) patients can develop thoracic aortic aneurysms (TAA) and therefore require serial imaging to monitor aortic growth. This study investigates the reliability of contrast-enhanced MR angiography (CEMRA) volumetry compared to two-dimensional diameter measurements to identify TAA growth. 1.2. Materials and Methods A retrospective, IRB approved and HIPAA compliant study was conducted on 20 BAV patients (45±8.9 years old, 20% women) who underwent serial CEMRA with a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…While earlier studies demonstrated aortic dilation rates of 1 to 2 mm/year [5], few patients are found to exhibit such rapid growth. A recent study by Trinh et al described diametric aortic growth of 0.06 cm/year [34]. This was corroborated by Detaint et al who found average annual maximum growth rates of 0.04 cm/ year (median 0.03 cm/year) as well as in Della Corte et al with average annual maximum growth rates of 0.06 cm/year [11,33].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While earlier studies demonstrated aortic dilation rates of 1 to 2 mm/year [5], few patients are found to exhibit such rapid growth. A recent study by Trinh et al described diametric aortic growth of 0.06 cm/year [34]. This was corroborated by Detaint et al who found average annual maximum growth rates of 0.04 cm/ year (median 0.03 cm/year) as well as in Della Corte et al with average annual maximum growth rates of 0.06 cm/year [11,33].…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies at our center using the same methods have investigated WSS, peak velocity, and aortic diameter and demonstrated excellent inter-observer reproducibility for all parameters [16,34,37]. The test-retest variability for region of interest analysis of systolic peak velocity and 3D WSS showed good agreement (Intra-class correlation coefficient ICC = 0.9 for velocity, and ICC = 0.8 for WSS) and a maximum difference of 0.04 m/sec for velocity and 0.05 Pa for WSS in a previously published study [37].…”
Section: Discussionmentioning
confidence: 80%
“…All subjects underwent a standard‐of‐care thoracic cardiovascular MRI exam including 2‐dimensional (2D) time‐resolved ECG gated (CINE) balanced steady state free precession imaging of the heart and aortic valve as well as 3D contrast‐enhanced magnetic resonance angiography following the administration of contrast media (either 0.2 mmol/kg of gadopentate dimeglumine, 0.1 mmol/kg of gadobenate dimeglumine, or 0.1 mmol/kg of gadofosveset trisodium) to provide a comprehensive evaluation of aortic morphology and valve function as previously reported 15, 16. In addition, 4D flow MRI (time‐resolved 3‐directional phase contrast MRI with 3D velocity encoding) was acquired in a sagittal oblique 3D volume covering the thoracic aorta using prospective ECG gating and a respiratory navigator gating 17.…”
Section: Methodsmentioning
confidence: 99%
“…contrast-enhanced magnetic resonance angiography following the administration of contrast media (either 0.2 mmol/kg of gadopentate dimeglumine, 0.1 mmol/kg of gadobenate dimeglumine, or 0.1 mmol/kg of gadofosveset trisodium) to provide a comprehensive evaluation of aortic morphology and valve function as previously reported. 15,16 In addition, 4D flow MRI (time-resolved 3-directional phase contrast MRI with 3D velocity encoding) was acquired in a sagittal oblique 3D volume covering the thoracic aorta using prospective ECG gating and a respiratory navigator gating. 17 4D flow pulse sequence parameters were as follows: spatial resolution=2.2 to 4.2 mm91.7 to 2.9 mm92.2 to 4.0 mm; field of view=320 to 470 mm9234 to 382 mm966 to 120 mm; temporal resolution=32.8 to 43.2 ms (11-31 cardiac time frames); echo time=2.1 to 2.8 ms; repetition time=4.1 to 5.4 ms; flip angle=7 to 15°.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Measuring the aortic diameter at predefined anatomic locations fails to capture interval growth at nonmaximal locations, and this measurement does not detect the components of aortic enlargement in circumferential or longitudinal directions. Height-/weight-adjusted aortic area has been proposed as a better predictor of future rupture than maximal diameter, and several studies have investigated the use of volumetric measurements of TAA and AAA to improve the sensitivity for detecting aortic growth ( 10 , 20 24 ). However, similar to diameter measurements, measurement of aortic area and volumetric should be performed at predetermined anatomic boundaries to ensure that measurements are comparable between studies, and small focal changes in aortic dimension may be camouflaged by a volumetric measurement approach.…”
Section: Introductionmentioning
confidence: 99%